A CASE STUDY: ADVOCATE THAT WORKED AS PERMANENT LECTURER ACCORDING TO LEGAL VIEW - Ramadhani, Arie (jfpublisher, 2022)
The dual position or profession as an advocate and a lecturer sometimes raises doubts about whether the dual position as a lecturer is allowed or not. This doubt has the potential to cause a debate that leads to legal uncertainty conditions. This study aims to determine the prohibition of a lecturer who also being an advocate and vice versa. Is there any prohibition on an advocate who also being a lecturer for eliminating the doubts and creating legal certainty for dual professions of lecturers and advocates. This research uses the normative research or library research method. Legal research conducted by examining library materials or secondary data through normative legal research, in this case referring to a court decision that has permanent legal force, the Decision No: 47/Pdt.SUS-PHI/2016/ PN Pdg. By doing this research, it is expected that it can further straighten the views or opinions that the dual profession of lecturers and advocates may or may not be based on the applicable positive law. From the results of this research, it was concluded that lecturers who were concurrently professions as advocates did not violate the legislation provisions and could not be justified to dismissal the double- professional lecturers.